4 Weeks Physical Literacy Program Using A Before–After School System (4 Week-BeAf School Program) Based on Artificial Intelligence Technology Powtoon Animation for Elementary School Children - Gustiawati, Resty (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
This research aims to develop a Physical Literacy program based on PowToon technology and AI Animation designed for elementary school students, using a four-week Before-After School approach. The program aims to improve students' understanding and physical skills through interactive and fun learning methods. In its development, the researcher used the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model, starting with an analysis of the need to find out the problems that exist in physical learning in elementary schools. Furthermore, the researcher designed a module combining PowToon technology and AI, so that learning materials can be delivered in a more interesting and easy-to-understand way for students. After the design and development stage, the program was piloted in three elementary schools in Subang Regency involving 70 students. The results of the study show that this program has succeeded in improving physical literacy, basic motor skills, and healthy lifestyles of students. With the use of PowToon technology and AI, the program has managed to provide a more enjoyable learning experience, which has a positive impact on increasing student engagement in physical activity. This is evident from the results of observations made by practitioners who show excellent judgment without any significant revision to the program. Expert validation tests provide a wealth of useful feedback for the refinement of the initial model, which is then revised to improve product quality. The results of observations and feedback from practitioners show that this program is very feasible to be implemented in elementary schools because it is in accordance with the characteristics of students and the needs of sports learning. This program has proven to be effective in supporting more interesting physical literacy learning and can be implemented well in the context of physical education in elementary schools. With these results, the 4Week-BeAf School Program can be an innovative and practical model in improving the quality of physical education at the elementary school level.